PENGARUH KOMITMEN ORGANISASI DAN LOCUS OF CONTROL TERHADAP PERILAKU REDUKSI KUALITAS AUDIT DAN KINERJA AUDITOR - Wahyuni, Sri (Sekolah Tinggi Ilmu Ekonomi Riau, 2019)
The purpose of this study is to determine the organization commitment, locus of control, auditor performance, audit quality reduction . The population in this study is the auditor at Public Accounting Firm second tiers in Indonesia. Collection of sample of 63 people. Data processing is done by SPSS software. The results show thatÂ organization commitment has a positive effect on audit quality reduction. Locus of control has a negative effect on audit quality reduction. Organization amd auditor performance has a negative effect on audit quality reduction. Locus of control has a positive effect on audit quality reduction